2021
DOI: 10.1161/jaha.121.021789
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Low‐Salt and High‐Potassium Diet on Arterial Stiffness and Left Ventricular Function in Indigenous Papuans

Abstract: Background A sodium‐restricted diet represents a potential non‐pharmacological strategy for improving blood pressure, arterial stiffness, and left ventricular (LV) diastolic function. We investigated age‐related differences in LV structure and function and the relationship between LV function and central hemodynamics in an indigenous Papuan population, who maintain a traditional lifestyle, including a low‐salt and high‐potassium diet. Methods and Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Although previous studies [23][24][25] have shown that high salt intake negatively impacts the response of resistant arteries to vasoactive agents, there was a lack of research focusing on the improvement effects of switching from a high-to low-salt diet in vivo. In a human study [26], found that salt reduction improved endothelium-dependent vasodilation [26] but did not improve arterial stiffness [27] and showed no impact on central and peripheral hemodynamics during exercise [28]. Perhaps it is quite impractical in human studies to design sophisticated procedures to observe the effects of salt restriction on vascular function.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies [23][24][25] have shown that high salt intake negatively impacts the response of resistant arteries to vasoactive agents, there was a lack of research focusing on the improvement effects of switching from a high-to low-salt diet in vivo. In a human study [26], found that salt reduction improved endothelium-dependent vasodilation [26] but did not improve arterial stiffness [27] and showed no impact on central and peripheral hemodynamics during exercise [28]. Perhaps it is quite impractical in human studies to design sophisticated procedures to observe the effects of salt restriction on vascular function.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has shown that high salt intake is one important contributor to left ventricular dysfunction and myocardial remodeling ( 1 4 ). Our findings are consistent with the existing evidence ( 1 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has shown that high salt intake is one important contributor to left ventricular dysfunction and myocardial remodeling ( 1 4 ). Our findings are consistent with the existing evidence ( 1 4 ). Salt intake was positively and independently correlated with hallmarks of left ventricular structure and function such as LVM, LVMI, LVRI, and Tei index, and negatively and independently correlated with LVFS and LVEF; however, it was impossible to clarify the causal relationship due to the inherent characteristics of a cross-sectional design.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations